2022
DOI: 10.3390/ijms23158779
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Basal and mTOR-Dependent Acute Pulmonary and Systemic Immune Response in a Murine Model of Combined Burn and Inhalation Injury

Abstract: Severe burn injury leads to a cascade of local and systemic immune responses that trigger an extreme state of immune dysfunction, leaving the patient highly susceptible to acute and chronic infection. When combined with inhalation injury, burn patients have higher mortality and a greater chance of developing secondary respiratory complications including infection. No animal model of combined burn and inhalation injury (B+I) exists that accurately mirrors the human clinical picture, nor are there any effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Downregulation of P70S6K after MSC-EV treatment compared to untreated mice also suggests that mTOR activation has been reduced (67). We have shown that the mTOR/PPARg axis is partly responsible for the acute and chronic (analogous to (68)(69)(70), and experiments are underway to determine if MSC-EV can modulate this response in an mTOR-dependent fashion. It is therefore tempting to speculate that a key component of the reprogramming capacity of MSC-EVs is mTOR dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Downregulation of P70S6K after MSC-EV treatment compared to untreated mice also suggests that mTOR activation has been reduced (67). We have shown that the mTOR/PPARg axis is partly responsible for the acute and chronic (analogous to (68)(69)(70), and experiments are underway to determine if MSC-EV can modulate this response in an mTOR-dependent fashion. It is therefore tempting to speculate that a key component of the reprogramming capacity of MSC-EVs is mTOR dependent.…”
Section: Discussionmentioning
confidence: 92%
“…To investigate the immunopathology of B+I, a significant comorbidity of burn injury that dramatically increases patient length-of-hospitalization and infection risk, we used a clinically relevant model of inhalation injury (12) using woodsmoke combined with our well-characterized murine model of a 20% TBSA, full-thickness contact cutaneous burn injury (24) to yield a combined B+I model (29). The combination of woodsmoke inhalation and a 20% TBSA injury causes an acute approximately 30% mortality rate within 24 hours of injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further limitation is that we have not defined the impact of immune reprogramming with CDDO-Me on clinically relevant outcomes such as infection control. We have recently published that our B+I mouse model does recapitulate the clinical picture of reduced control of Pseudomonas infection (29), and we are currently testing the impact of NRF2 deficiency and activation in this bacterial infection model. Testing of this therapeutic benefit, a better understanding of the dosage and timing of CDDO-MP administration after injury, and drug toxicity will be required before clinical application can be considered.…”
Section: Discussionmentioning
confidence: 99%